Lowering of lipid composition in aorta of guinea pigs by Curcuma domestica - Mohammad Jamaludin J; Abdul-Lati; Ahmad-Raus Raha R (BMC, 2001)
Abstract Background A short-term study was carried out using guinea pigs to determine the effects of Curcuma domestica on lipid composition in the serum and aorta. Methods Animals were given food pellets containing 4% (w/w) powdered rhizome of C. domestica in order to determine its effect on cholesterol, triglyceride and phospholipid levels in the aorta and serum. The animals were fed either a cholesterol free diet or a high cholesterol diet (2% cholesterol, w/w, in food pellet) in order to induce hypercholesterolemia.. After five weeks of this diet treatment, blood and aorta were taken for biochemical analysis and histological studies. Results C. domestica in the diet showed no significant effect on the levels of cholesterol, triglyceride and phospholipid in the serum and aorta of the cholesterol free diet animals. However, addition of C. domestica to a high cholesterol diet counteracted increases in the levels of cholesterol, triglyceride and phospholipid in the aorta. Histology studies showed less cholesterol deposits in the aorta of high cholesterol diet animals given C. domestica compared to the high cholesterol diet animals not given C. domestica supplement. C. domestica also had a lowering effect on triglyceride level in the serum of high cholesterol diet animals but showed no effect on serum cholesterol and phospholipid levels. Conclusion This study has shown that dietary intake of C. domestica decreased all lipid composition levels in the aorta and also the serum triglyceride level. In addition, C. domestica also reduced cholesterol deposition in the aorta of high cholesterol diet animals.